AfricArXiv – the pan-African Open Scholarly Repository (Overview and Roadmap) - Ahinon, Justin, Sègbédji; Arafat, Hisham; Ahmad, Umar Salisu; Achampong, Joyce; Aldirdiri, Osman; Ayodele, Obasegun, Tekena; Bezuidenhout, Louise; Okelo, Luke; Cary, Michael; Fath, Nada; Ksibi, Nabil, Aziz; Zimmer, Niklas, Carl; et al. (My University, 2020)
AfricArXiv is a community-led digital archive for African research working towards building an Africa-owned open scholarly repository; a knowledge commons of African scholarly works. We are partnering with established scholarly repository services to provide a platform for African scientists of any discipline to present their research findings and connect with other researchers – on the African continent and globally. It is our aim to promote discoverability of African research output according to sfDORA : https://sfdora.org/read/ FAIR principles: https://www.go-fair.org/fair-principles/ Helsinki Initiative on Multilingualism: https://www.helsinki-initiative.org/en To contextualize the above to the African scholarly community we have postulated 10 African Principles for Open Access in Scholarly Communication: https://info.africarxiv.org/african-oa-principles/
Keywords: Africa; African research; AfricArXiv; discoverability; language diversity; open access; open science; preprint repository; roadmap; scholarly communication